Analysing the geothermal project life cycle by using the design structure matrix - Witt, Magnus de 1988- (2015)
This thesis reviews whether the project life cycle of a geothermal power project in Iceland could be mapped and represented in a common way. Is there any space for improving the project life cycle and is the design structure matrix (DSM) an appropriate tool for it? The basis of this study is the general project life cycle theory combined with the theory of economic clusters; the DSM theory is used for this. The cluster gives the geothermal field in Iceland a competitive advantage and the life cycle theory should give a common overall framework to execute geothermal projects in Iceland. As a starting point an already existing DSM model was used - the DSM was from 2013 and a result of the Iceland geothermal cluster workshops. For gathering more detailed and Iceland specific information experts from the files were interviewed. The gathered information was used as input for updating the existing DSM model. The DSM model was manipulated according to the theory of the sequencing and banding algorithm. The result was a new project life: this new project life cycle is more efficient than the previous one. The DSM was the major tool in the optimization process and helped to find an optimal project life cycle for geothermal power projects in Iceland.